Analysis of the Effect of Delay Time and Type of Coolant Media with the Spray Method on the Back Surface of PV Panel - Ansyah, Pathur Razi; Hartoyo, Muhammad Hendrawan Septian; Budianto, Akhmad Ghiffary; Cahyono, Gunawan Rudi; Subagyo, Rachmat (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2024)
Sunlight can be harnessed as a clean and renewable energy source using solar cells and the photovoltaic process. However, relying on direct sunlight exposure can increase solar cell temperatures and negatively impact performance. This research aims to maintain cell efficiency by exploring the effectiveness of spraying coolant media on the bottom surface of panels through three timed intervals (10, 20, and 30 minutes) using three different media (A, B, and C). Each spray application lasts for 1 minute. Analyzing the test results with Minitab18 software with full factorial design will identify the most effective treatment for maintaining performance. Based on the results of the experimental test, coolant A with a 10-minute delay spraying time has a maximum power of 52.89 Watts, a temperature of 48oC, and an efficiency of 5.69%. Response Optimization using Design of Experiment (DOE) Full Factorial shows an optimal response with coolant A and a 10-minute delay spraying time with the lowest temperature at 49.3oC, maximum output power at 46.87 Watts, and efficiency at 5.61%. Moreover, Tukey Krammer test result provides an information about 10-minute delay spraying time has a better performance to reduce the PV panel temperature compared to 30-minute delay spraying time by 3.94 oC.